Lack of information on colorectal cancer in general public might be the reason for low response rates to screening progam - Mara Bebek; Sanja Langer; Lana Botak; Petar Jazbec; Vesna Ramljak; Ivan Milas (Libri Oncologici, 2022)
Introduction: In Croatia, about 3,500 patients are diagnosed with a colorectal carcinoma annually. The National Program for Early Detection of Colon Cancer has been implemented in Croatia since 2007. The program’s primary goal is todetect colon cancer at an early stage of the disease, which should reduce the incidence and mortality from colon cancer. Aim: To determine the interest of the target group in participating in the program, reasons for not responding to the program, and their knowledge about it altogether. Materials and methods: Surveying 50 patients within the program’s target group about their response to and understanding of reasons for screening. Results: Although 84% of the participants know about the program, the response rate was unsatisfactory. Conclusion: Most of the respondents who suffered from a colorectal carcinoma received a call but did not respond due to the absence of symptoms, which correlates with a low level of knowledge on colorectal carcinoma.